The TMEM106B T186S coding variant increases neurite arborization and synaptic density in primary hippocampal neurons - Nguyen, Quynh; Wood, Caleb A.; Kim, Peter J.; Jankowsky, Joanna L. (Frontiers in Neuroscience, 2023)
The lysosomal protein TMEM106B was identified as a risk modifier of multiple dementias including frontotemporal dementia and Alzheimer’s disease. The gene comes in two major haplotypes, one associated with disease risk, and by comparison, the other with resilience. Only one coding polymorphism distinguishes the two alleles, a threonine-to-serine substitution at residue 185 (186 in mouse), that is inherited in disequilibrium with multiple non-coding variants. Transcriptional studies suggest synaptic, neuronal, and cognitive preservation in human subjects with the protective haplotype, while murine in vitro studies reveal dramatic effects of TMEM106B deletion on neuronal development. Despite this foundation, the field has not yet resolved whether coding variant is biologically meaningful, and if so, whether it has any specific effect on neuronal phenotypes. Here we studied how loss of TMEM106B or expression of the lone coding variant in isolation affected transcriptional signatures in the mature brain and neuronal structure during development in primary neurons. Homozygous expression of the TMEM106B T186S variant in knock-in mice increased cortical expression of genes associated with excitatory synaptic function and axon outgrowth, and promoted neurite branching, dendritic spine density, and synaptic density in primary hippocampal neurons. In contrast, constitutive TMEM106B deletion affected transcriptional signatures of myelination without altering neuronal development in vitro. Our findings show that the T186S variant is functionally relevant and may contribute to disease resilience during neurodevelopment.